2020
DOI: 10.1101/2020.01.13.903765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of a resistance gene against a fungal pathogen on the plant host residue microbiome: the case of theLeptosphaeria maculans-Brassica napuspathosystem

Abstract: Oilseed rape residues are a crucial determinant of stem canker epidemiology, as they support the sexual reproduction of the fungal pathogen Leptosphaeria maculans. The aim of this study was to characterise the impact of a resistance gene against L. maculans infection on residue microbial communities and to identify micro-organisms interacting with this pathogen during residue degradation. We used near-isogenic lines to obtain healthy and infected host plants. The microbiome associated with the two types of pla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 64 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Microbiome studies revealed that pathogenic microbes highly impact microbial community structures [2]. In addition to microbiome communities, the proliferation of plant pathogens is influenced by microbial environmental conditions and host resistotypes [12,23,55]. Due to the availability of large numbers of samples, we could perform a downstream analysis implementing leaf symptoms for microbiome samples from wild tomatoes in Canta.…”
Section: Compositional Changes Of Microbes Upon Dysbiosis In Cantamentioning
confidence: 99%
“…Microbiome studies revealed that pathogenic microbes highly impact microbial community structures [2]. In addition to microbiome communities, the proliferation of plant pathogens is influenced by microbial environmental conditions and host resistotypes [12,23,55]. Due to the availability of large numbers of samples, we could perform a downstream analysis implementing leaf symptoms for microbiome samples from wild tomatoes in Canta.…”
Section: Compositional Changes Of Microbes Upon Dysbiosis In Cantamentioning
confidence: 99%
“…However, in this study the pseudothecia produced on stubble were not distinguished as L. biglobosa or L. maculans. Recent work showed that L. biglobosa is a key species in microbial communities on oilseed rape stubble, whereas L. maculans plays a minor role (Kerdraon et al, 2020). Additionally, L. biglobosa is more competitive than L. maculans at the necrotrophic growth stage on stem stubble (West et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…maculans promote colonization by L . biglobosa (Kerdraon et al, 2020). This suggests that use of cultivars with good resistance against L .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations